Narrative virtue of autobiography: the mnemonic trace in a group of nurses - Ana Piera Orts (Universidad de Alicante, 2012)
From personal narratives, which were developed by nursing experts, a textual analysis. In the theoretical section the reader is on the keys of a qualitative, inductive and ideographic and presents the reflective path followed from autobiographical fragments on the socialization process by which these professionals have developed. The working hypothesis started from the declarative or episodic memory for the recovery of experiences and events, from the reproduction of what has been experienced in the initiation stage. During the work revealed the presence of an insistent forgetting that gave way to the track mnemic, absences as a sign that open a path towards ethnographic literature. Some examples of this neglect by presenting a great narrative. This is the virtue that helps the time to live as a story and it's time settings. Through these texts shows that during the initial stage of practice, there are unique processes that are similar to those in the professional integration. The materials are certainly worked vivid texts, generating space for the narrator's own self, as for the analytical ethnographer.